Factors Influencing the Adoption of Online Health Consultation Services: The Role of Subjective Norm, Trust, Perceived Benefit, and Offline Habit - Gong, Zepeng; Han, Ziqiang; Li, Xudan; Yu, Chao; Reinhardt, Jan D. (Frontiers in Public Health, 2019)
The cyberspace plays an important role in improving the quality, equity, and efficiency of health services. Studying people's adoption of online health services, such as online health consultation services (OHCS) can benefit both industry and policy in the health service sector. This paper investigates influencing factors and paths of people's intention of adopting OHCS by employing the extended valence framework, with our new contribution of integrating subjective norm and offline habit into the model. Five hundred forty-three university students participated in the survey. Structural equation models and Sobel-Goodman tests were applied to test the models. The results show that subjective norm (β = 0.077, p = 0.041), trust in providers (β = 0.194, p = 0.002) and perceived benefit (β = 0.463, p < 0.001) positively affect the intention to adopt OHCS, while offline habit (β = −0.111, p = 0.026) has a negative effect. However, the association of perceived risk (β = −0.062, p = 0.315) and adoption is not supported. Moreover, trust in providers plays a mediating role between subjective norm and the intention of adopting, while perceived benefit mediates the relationship between trust in providers and the intention of adopting. This study highlights the importance of trust, subjective norm, perceived benefit, and persisting habits in promoting the adoption of OHCS.